Youth constructing their identities in the English language classrooms: lesson study from elected secondary schools in Malaysia - Idrus, Faizah (Partridge, 2021)
Identity construction is inevitable no matter where we are. This book draws on how youth construct their identity at different situation, places and time. Thus, the content of the book is applicable to any youth, parents, teachers or academics. The core of the book revolves around how lesson studies are used to exemplify how these youngsters ‘want’ to be identified and known. These lesson studies are used in language classes particularly the Malaysian Literature and narratives used in these classes are mostly written by local writers. In the same vein, it also discusses the philosophy behind identity construction. The notion of Third Space is apt as in this context, Youth and ‘Third Space’ are inextricably linked. This book is different from the rest of identity construction books as the lesson studies are real and happened in real classrooms. There will be vignettes in which stories are told and other youth could relate with and perhaps find solace in that they are no different from others out there. Potential readers will range from high-schoolers, teachers, academics, curriculum developers, parents and guardians as well as anyone for leisure reading. This book proposes the need to construct a shared youth identity, starting from the classroom, which is facilitated by teachers through the use of Malaysian short stories.